2019
DOI: 10.5603/oj.2019.0016
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of retinal and optic disc vascular perfusion density in retinitis pigmentosa patients by optical coherence tomography angiography

Abstract: BaCKground:The aim of the study was to evaluate the vascular flow density measured by optical coherence tomography angiography in patients with retinitis pigmentosa and to compare it with normal subjects. MateriaL and Methods: This was a cross-sectional case control study employing 16 eyes of eight patients with retinitis pigmentosa and 16 eyes of eight healthy subjects. Optical coherence tomography angiography was performed in all subjects. The macula was imaged with a 3 × 3 mm scan, whereas for the optic ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Another study showed that mean RNFL thickness and W-RPC VD were significantly lower in the non-arteritic anterior ischemic optic neuropathy (NAION) group compared to normal group [ 35 ]. Patients with retinitis pigmentosa showed a decreased ONH VD compared with healthy subjects [ 36 ]. In the present study in all segments VD measurements are significantly less in DM than normal control.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that mean RNFL thickness and W-RPC VD were significantly lower in the non-arteritic anterior ischemic optic neuropathy (NAION) group compared to normal group [ 35 ]. Patients with retinitis pigmentosa showed a decreased ONH VD compared with healthy subjects [ 36 ]. In the present study in all segments VD measurements are significantly less in DM than normal control.…”
Section: Discussionmentioning
confidence: 99%